Opioids and the Risk of Motor Vehicle Collision: A Systematic Review. (February 2022) - Leon, Silvia J.; Trachtenberg, Aaron; Briscoe, Derek; Ahmed, Maira; Hougen, Ingrid; Askin, Nicole; Whitlock, Reid; Ferguson, Thomas; Tangri, Navdeep; Rigatto, Claudio; Komenda, Paul
Background: Opioid analgesics are among the most commonly prescribed medications, but questions remain regarding their impact on the day-to-day functioning of patients including driving. We set out to perform a systematic review on the risk of motor vehicle collision (MVC) associated with prescription opioid exposure.Method: We searched Medline, PubMed, EMBASE, Scopus, and TRID from January 1990 to August 31, 2021 for primary studies assessing prescribed opioid use and MVCs.Results: We identified 14 observational studies that met inclusion criteria. Among those, 8 studies found an increased risk of MVC among those participants who had a concomitant opioid prescription at the time of the MVC and 3 found no significant increase of culpability of fatal MVC. The 3 studies that evaluated the presence of a dose-response relationship between the dose of opioids taken and the effects on MVC risk reported the existence of a dose-response relationship. Due to the heterogeneity of the different studies, a quantitative meta-analysis to sum evidence was deemed unfeasible. Our review supports increasing evidence on the association between motor vehicle collisions and prescribed opioids. This research would guide policies regarding driving legislation worldwide.Conclusion: Our review indicates that opioid prescriptions are likely associated with an increased risk of MVCs. Further studies are warranted to strengthen this finding, and investigate additional factors such as individual opioid medications, opioid doses and dose adjustments, and opioid tolerance for their effect on MVC risk.